Determinación de Costos por orden de producción de los desayunos sorpresa de la tienda virtual “Detallitos Tarará” (2022)
The virtual store "Detallitos Tarará" with optimal performance in the service sector, downtown its operation to the production and marketing of food for breakfast that will from the range of confectionery, prepared and packaged foods or products made with prefabricated supplies in the market such as hot and cold drinks, waffles and pancakes, andwiches and fruit salads, especially distinguished by the use of innovation and the ability to face the many changes in the business environment.